On issues of contemporary phraseology: rozwalić system - Kosek, Iwona (Papers in Linguistics, 2025)
The article discusses an expression not included in phraseological dictionaries, namely rozwalić system (lit. ‘to blow up the system’). It appears in Internet comments, especially on videos on the YouTube channel, on Instagram and on Facebook. The study attempts to describe semantic and syntactic properties of the phrase and to trace the metaphorisation process of the initial syntactic combination. As a result of the analysis, it is proposed to distinguish two homonymic units of the form ktoś, coś rozwala/rozwali system (‘someone, something blows up the system’): 1. ‘someone, something is excellent, the best,’ 2. ‘someone, something is unexpected, unconventional.’ It is not clear how the two meanings developed. The latter might be motivated by the language of computer gamers, but in the absence of textual attestation in that language, this is only a hypothesis.